FINANCIAL FEASIBILITY ANALYSIS OF SEMI-INTENSIVE SHRIMP FARMING IN CIHERAS VILLAGE, TASIKMALAYA - Rayhan Zein; Ine Maulida; Ibnu Dwi Buwono; Atikah Nurhayati (Universitas Mataram, 2025)
This study aims to analyze the economic feasibility of vaname shrimp farming (Litopenaeus vannamei) with a semi-intensive system in Ciheras Village, Tasikmalaya Regency. Data collection technique was conducted by census method on 10 shrimp farmers representing semi-intensive cultivation technology. Data collected include investment costs, operating costs, production results, and receipts from shrimp sales. Financial analysis is carried out through four main indicators, including profit (profit), Revenue Cost Ratio (R/C), Break Even Point (BEP), and Payback Period (PP). The results showed that the average net profit obtained by farmers per cycle reached Rp58, 750, 000. The pond business in Ciheras village was declared feasible based on financial feasibility test (Revenue Cost Ratio 1.35; Payback Period 2.54 years, and Break Even Point Rp413, 501, 004 per year). The implementation of pond operations in the rainy season is more profitable than the dry season with a value of Revenue Cost Ratio of 1.64; Payback Period of 2.82 years, and Break Even Point of Rp134, 576, 392. This finding shows that semi-intensive vaname shrimp farming in Ciheras Village is not only economically feasible, but has the potential to improve the welfare of coastal communities. One of the important keys to the profitability of this semi-intensive farm emphasizes the importance of production cost efficiency, especially in feed and fry components. The final result of this research is expected to be a reference for Pond operations for farmers, investors, and local governments.